TEACHING WITH PROJECTS: FROM EXPECTATIONS TO REALITY AT UPPER SECONDARY SCHOOLS IN HANOI = TỪ KỲ VỌNG TỚI THỰC TẾ : DẠY HỌC VỚI DỰ ÁN TẠI CÁC TRƯỜNG THPT Ở HÀ NỘI - Phạm, Phúc Thành (2020)
The thesis attempts to investigate how teachers apply the project based on the Pilot English textbooks into teaching English at upper secondary schools in Hanoi. After the preliminary investigation and the literature review, it was found out that using project in the the language classroom is one of the effective methods to help students develop not only language skills but also other necessary skills in real life. The study aims to examine (1) the benefits of projects, (2) the difficulties of teachers when teaching with projects and (3) the solutions to those problems. The data was gathered from English teachers who teach projects at upper secondary schools in Hanoi. The researcher made use of questionnaire and interview to create a different source of data. The result of the study revealed that the project in the the language classroom offered many benefits to students in terms of developing skills, especially language skills. It also showed that most difficulties of teachers stem from students’ poor learning skills and their learning attitudes. However, teachers are always active in finding solutions to those problems.